2017
DOI: 10.1016/j.amjcard.2016.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes After Stent Implantation for Left Main Coronary Artery (from the Multicenter Assessing Optimal Percutaneous Coronary Intervention for Left Main Coronary Artery Stenting Registry)

Abstract: We assessed long-term outcomes after left main coronary artery (LMCA) stenting based on lesion types and stenting strategies. In the Assessing Optimal percutaneous coronary Intervention for Left Main Coronary Artery stenting registry, we evaluated 1,607 consecutive patients undergoing stent implantation for unprotected LMCA lesions (bifurcation lesions: n = 1318 and nonbifurcation lesions: n = 289). Among the bifurcation lesions, 1,281 lesions were treated with stenting across the bifurcation (bifurcation 1-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 23 publications
1
17
1
Order By: Relevance
“…3,14-17 In particular, patients with ACS and cardiogenic shock exhibited 40% in-hospital mortality after PCI. 1,9 In this study, the 180-day mortality of patients with ACS with shock was 49.5%, which corroborated previous reports. 1 However, the 180day mortality of the ACS without shock group was 8.6%, which was much lower than in the ACS with shock group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3,14-17 In particular, patients with ACS and cardiogenic shock exhibited 40% in-hospital mortality after PCI. 1,9 In this study, the 180-day mortality of patients with ACS with shock was 49.5%, which corroborated previous reports. 1 However, the 180day mortality of the ACS without shock group was 8.6%, which was much lower than in the ACS with shock group.…”
Section: Discussionsupporting
confidence: 91%
“…The details of the definitions used in this study were reported previously. 9 We defined unprotected LMCA disease as angiographically significant stenosis of the LMCA without patent surgical grafts to the left coronary artery system. We defined cardiogenic shock as Killip class 4 at presentation, indicating systolic blood pressure <90 mmHg and manifestations of hypoperfusion such as oliguria, cyanosis and diaphoresis.…”
Section: Definitions and Clinical Outcomesmentioning
confidence: 99%
“…The AOI-LMCA (Assessing Optimal percutaneous coronary Intervention for Left Main Coronary Artery) stenting registry is a retrospective, multicenter registry that enrolled 1809 consecutive patients who underwent LMCA stenting with bare-metal stents or DES in 6 Japanese hospitals experienced with LMCA stenting between November 2004 and December 2012. The protocol and details of patient enrollment have been described elsewhere [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…Secondary outcome measures included all-cause death, cardiac death, sudden death, MI, definite or probable ST, stroke, any coronary revascularization, or major adverse cardiovascular events (MACE: cardiac death, MI, or TLR) at 5-year. Definitions for each endpoint have been previously described in detail [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation